Contributions of volatile and nonvolatile compounds (at 300°C) to condensational growth of atmospheric nanoparticles: An assessment based on 8.5 years of observations at the Central Europe background site Melpitz. Issue 1 (14th January 2017) - Wang, Zhibin; Birmili, Wolfram; Hamed, Amar; Wehner, Birgit; Spindler, Gerald; Pei, Xiangyu; Wu, Zhijun; Cheng, Yafang; Su, Hang; Wiedensohler, Alfred
Abstract: Long‐term measurements of particle number size distributions in combination with thermodenuder analysis have been performed since July 2003 at the Central European station of Melpitz, Germany. Up to the end of 2011, 20% of all investigated days during the 8.5 years of measurements showed new particle formation and subsequent growth. To investigate the role of various chemical compound candidates for condensational nanoparticle growth, we focused on nucleation events in which the measured size distributions with and without thermodesorption both showed growth patterns (accounting for up to 85% of all nucleation events). In this study, particulate compounds that volatilize at 300°C were specifically defined as "volatile, " in contrast to "nonvolatile" compounds, which remain in the particulate phase after being heated to 300°C. A strong correlation between ambient temperature and growth rate associated with volatile substances (except gaseous sulfuric acid) was found, which implies the importance of organics (possibly oxidized biogenic organic compounds) in particle growth at Melpitz. The contributions of the volatile compounds to the growth rate due to condensation of gaseous sulfuric acid and organics were found to be about 19% and 47%, respectively. The remaining 25% was attributed to nonvolatile residuals, which appear to form gradually during the particle growth process and are characterized as extremely low‐volatility compounds. The growth rate associated with volatile components exhibited significant seasonal variation, with the highest value during summertime, whereas the growth rate associated with the nonvolatile fraction showed less fluctuation. Key Points: Nonvolatile residuals persistently contribute to new particle formation and subsequent growth at Melpitz Contributions of sulfuric acid and nonvolatile compounds to particle growth rate are comparable Biogenic volatile organic substances (evaporating at 300°C) were estimated to explain approximately half of the nanoparticle growth